Special Education Teachers’ Perceptions on Using Technology for Communication Practices - Siyam, Nur (2018)
An important aspect to the effective education of students with special educational needs and disabilities (SEND) is the successful coordination between all stakeholders (parents, educators and therapists). The present study employed qualitative methods to investigate teachers’ perceptions on the current communication practices and how they can be improved using technology. Nine special education teachers participated in semi-structured interviews. Teachers in the study used both traditional and, to a lesser degree, technological means of communication. Technological methods included instant messaging, the school’s information system, and electronic Individualized Education Programs (IEPs) shared on the cloud. The data revealed that some special education teachers were content with the current methods of communication, while others perceived the introduction of new technology useful for the improvement of the communication process. Results can be used to identify the requirements needed before developing and launching new innovations for communication between parties involved with the intervention of SEND students.